#### Answer

$\dfrac{3+6(8-5)}{4^{2}+2}=\dfrac{7}{6}$

#### Work Step by Step

$\dfrac{3+6(8-5)}{4^{2}+2}$
Our first step wil be to perform the operation inside the parentheses in the numerator and to evaluate the exponential expression in the denominator:
$\dfrac{3+6(8-5)}{4^{2}+2}=\dfrac{3+6(3)}{16+2}=...$
Now, in the numerator, evaluate the product and after that, the sum. In the denominator, evaluate the sum. At the end, simplify if possible:
$...=\dfrac{3+18}{18}=\dfrac{21}{18}=\dfrac{7}{6}$